MASSAGE EFFLURAGE PENGARUH MASSAGE EFFLURAGE TERHADAP SKALA NYERI DISMENORE PADA REMAJA PUTRI DI SMK CITRA MEDIKA SRAGEN: PENGARUH MASSAGE EFFLURAGE TERHADAP SKALA NYERI DISMENORE PADA REMAJA PUTRI DI SMK CITRA MEDIKA SRAGEN - Ulkhasanah, Muzaroah Ermawati; Rosida, Umi; Prakoso, Adi Buyu (STIKES ADVAITA MEDIKA TABANAN, 2024)
Background: Dysmenorrhea is a medical term for pain during menstruation. Pain is a sensory and emotional experience associated with actual or potential tissue damage that is felt when the damage is actually occurring. A non-pharmacological way to relieve pain is to use a safe massage efflurage technique. This study aims to compare the pain scores of female students who experience dysmenorrhea before and after undergoing therapy. Methods: This study used an experimental methodology and a one group pretest-posttest design with a pre-experimental design. The Numeric Rating Scale (NRS) is the instrument used. For two consecutive days the sample received massage efflurage therapy for 15 minutes. Results: The average pain before the effleuragee massage was moderate, after the effleuragee massage the pain was reduced and became a moderate scale. Conclusion: According to research findings, massage efflurage therapy helps young women at SMK Citra Medika Sragen to reduce pain due to dysmenorrhea.